Hubungan Antara Iklim Organisasi Dengan Kepuasan Kerja - Riyadi, Oscar Dian; , Taufik. S.Psi, M.Si. Ph.D (2015)
Every company or organization in achieving its goals requires good cooperation between employees and the company. Good cooperation based on honesty, firmness, fairness, mutual respect and mutual interests between employees and the company in order to create a positive organizational climate conducive to employees that increase employee job satisfaction. This study aims to examine the relationship between organizational climate and job satisfaction, employee satisfaction levels, the level of employee organizations climate, knowing the role of organizational climate on job satisfaction. The hypothesis is a positive relationship between organizational climate and job satisfaction. The population in this study is a FIF Solo Baru employees totaling 133 employees, obtained a sample of 100 respondents, referring to the opinion Roscoe (1975) with sampling techniques using simple random sampling technique. Data collection method used is the scale of organizational climate and job satisfaction scale. Based on the analysis of data can be obtained that the product moment correlation rxy value of 0,376; p = 0,000 (p < 0,01), this means that there is a relationship between organizational climate and job satisfaction. Effective contribution between organizational climate on job satisfaction of 0,141 which means that job satisfaction can be explained by the organizational climate of 14,1%, while the remaining 85,9% was contributed by other variables not examined. The conclusion of this study is that there is a significant positive relationship between organizational climate and job satisfaction. The higher a person's organizational climate it is increasingly steeper also job satisfaction and vice versa. Keywords: Climate organization, Job Satisfaction